An NF-κB-Dependent Survival Pathway Protects against Cell Death Induced by TVB Receptors for Avian Leukosis Viruses - Chi, Yuling (American Society for Microbiology, 2002)
TVB receptors are death receptors of the tumor necrosis factor receptor (TNFR) family and serve as cellular receptors for cytopathic subgroups B and D and noncytopathic subgroup E of the avian leukosis viruses (ALVs). Although TVB is essential for ALV-B-mediated cell death, binding of the ALV-B envelope protein to its cognate receptor TVB activates cell death only in the presence of protein biosynthesis inhibitors, which presumably block the expression of protective factors. In the case of TNFR-1, the main antiapoptotic pathway depends upon nuclear factor kappa B (NF-κB)-activated survival factors. Here we show that overexpression of TVB receptors in human 293 cells activates NF-κB via a mechanism involving the cytoplasmic death domains of these receptors. NF-κB is also activated upon binding of a soluble ALV-B or ALV-E surface envelope-immunoglobulin fusion protein to the cognate TVB receptors and by ALV-B infection of a chicken embryo fibroblast cell line (DF1). Importantly, the cycloheximide requirement for TVB-dependent cell death was overcome by the expression of a transdominant form of IκB-α, and downregulation of NF-κB by the immunomodulator pyrrolidinedithiocarbamate enhanced the cytopathogenicity of ALV-B. These results demonstrate that TVB receptors trigger NF-κB-dependent gene expression and that NF-κB-regulated survival factors can protect against virus-induced cell death.